FRI0190 Surgical treatment for gastroesophageal reflux disease in systemic sclerosis. (1st June 2001) - Sampaio-Barros, PD; Andreollo, NA; Lopes, LR; Cunha, AG; Samara, AM; Brandalise, NA; Marques-Neto, JF
Abstract : Background: Objectives: To describe the experience with the surgical treatment for gastroesophageal reflux disease (GRD) in systemic sclerosis (SSc). Methods: From 202 patients with the diagnosis of SSc attended at the Scleroderma outpatient clinic in the period 1991–2000, ten patients (5%) who presented GRD, with severe chronic esophagitis and stricture, were submitted to surgical treatment. All the patients were female and eight were Caucasian, with seven presenting limited SSc (mean age 53 years and mean disease duration 17 years) and three diffuse SSc (mean age 44 years and mean disease duration 6 years). Results: The correction of the gastroesophageal reflux was performed through videolaparoscopy in nine patients. Seven patients underwent modified Nissen technique and three patients Lind technique. There was satisfactory clinical response, with significant improvement in the heartburn and dysphagia in all the patients. After a mean followup of 34 months (12–76 months), one patient presented clinical relapse (after 54 months) and another patient needed a surgical ressection of a paraesophageal hernia (Y-Roux). Conclusion: The surgical treatment of GRD represents an efficient therapeutic option in SSc patients with severe esophagitis and stricture.